Development Of Nano-Formulation Using Pvp/P407 Based On Solid Dispersion From Standardised Ethanolic Extract Of Orthosiphon Stamineus Leaf For Solubility And Oral Bioavailability Improvements - Saidan, Noor Hafizoh (2017)
This study involved the quality assessment of Orthosiphon stamineus raw materials, standardisation of different extracts, development of nano-formulation using macerated ethanolic extract and evaluated for selected biological activities (antioxidant and cytotoxicity). The dried leaves of O. stamineus fulfilled the physicochemical properties, heavy metals and microbial limits to be used for further study. Five different extracts namely methanolic, methanolic (50%), ethanolic, ethanolic (50%) and water were obtained using three different techniques (Soxhlet, reflux and maceration). The spectroscopic (FTIR and UV) and chromatographic (HPLC) analysis were carried out for standardisation of the crude extracts.